A Lightweight Symmetric Cryptography Scheme for Identifying Compromised Node in WSN - Yassine Maleh; Abdellah Ezzati (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Wireless Sensor Network (WSN) is consisting of independent and distributed sensors to monitor physical or environmental conditions, such as temperature, sound, pressure, etc. The most crucial and fundamental challenge facing WSN is security. Due to minimum capacity in-term of memory cost, processing and physical accessibility to sensors devices the security attacks are problematic. They are mostly deployed in open area, which expose them to different kinds of attacks. In this paper, we present an illustration of different attacks and vulnerabilities in WSN. Then we proposed a new lightweight cryptography algorithm for identifying compromised node in WSN called Leap Enhanced. Our evaluations on TOSSIM give a precise and detailed idea of the extra cost of consumption of resources needed to ensure the high level of expected security compared to other cryptography schemes in literature.